Tender morsels - Lanagan, Margo, 1960- (Alfred A. Knopf, 2008)
A young woman who has endured unspeakable cruelties is magically granted a safe haven apart from the real world and allowed to raise her two daughters in this alternate reality, until the barrier between her world and the real one begins to break down.